Rutas y protocolos para la inclusión educativa de estudiantes con necesidades educativas especiales asociadas a la reducción de la movilidad en la Universidad Nacional de Chimborazo. - Carrillo Vega, Margarita Azucena (2025)
Educational inclusion procedures and protocols for students with special educational needs associated with reduced mobility is a challenge for the National University of Chimborazo (UNACH), presenting architectural, pedagogical and social barriers that hinder the full participation of these students, violating their right to an equal and accessible education. This document proposes procedures and protocols to guarantee their inclusion, focusing on identification, accessibility and follow-up. The main aim was to design inclusive strategies that address the needs of this student population and promote an equal academic environment. This methodology included surveys and interviews with university officials, complemented by an analysis of the Ecuadorian legislative framework. These tools made it possible to identify specific barriers, evaluate current practices, and develop guidelines for effective participation. The results demonstrate that the majority of respondents participating in the research experienced significant limitations in institutional infrastructure and processes. Moreover, there was a lack of training in inclusion issues for teaching and administrative staff. There was a consensus among interviewees on the need to create timely and clear identification procedures and protocols to facilitate accessibility and ongoing support. In conclusion, UNACH needs the implementation of a solid inclusive policy that guarantees the right to education for students with disabilities. The suggested procedures and protocols respond to these needs from a holistic perspective, promoting accessibility, awareness and strengthening of the university community in values of equality and respect for diversity.